2023
DOI: 10.26713/cma.v14i2.2153
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Surveillance Drone System for Health Care Enhancement in a Smart City

Loai Kayed B. Melhim

Abstract: Accelerating medical services to provide appropriate health care within the available time is essential, especially in critical cases. Achieving this goal depends on the response speed of the health care teams in reaching the accident scene and the people who are seeking or needing health care services. Response speed depends entirely on the data provided to these teams by the requesters of these services. This work utilizes drone technologies through a set of developed algorithms to ensure the provision of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A qualitative review of the corpus found two emerging themes. These were research into the application of drones for the delivery of time-critical medical items [13,14] and research into drones for the delivery of non-time-critical medical items [15,16]. The difference between these two applications is that the delivery of time-critical medical items by drone is generally in response to an emergency [17].…”
Section: Resultsmentioning
confidence: 99%
“…A qualitative review of the corpus found two emerging themes. These were research into the application of drones for the delivery of time-critical medical items [13,14] and research into drones for the delivery of non-time-critical medical items [15,16]. The difference between these two applications is that the delivery of time-critical medical items by drone is generally in response to an emergency [17].…”
Section: Resultsmentioning
confidence: 99%